Implementing Design Thinking for UI/UX Optimization: Insights from PT. Asuransi Simas Jiwa - Vivi Rahayu; Ika Kurniawati; Fachri Amsury; Heriyanto Heriyanto (TIERS Information Technology Journal, 2024)
PT Asuransi Simas Jiwa is one of the companies that has implemented a fairly good information system in carrying out business processes. Siji Sales Force is a website-based information system used by Sales Agents to create, design and manage digital marketing activities. Based on the data collection results, it is known that several problems with the Siji Sales Force Web include shortcomings in terms of the appearance and functionality of the website. Based on observations of the features in the report menu, errors often occur and there has been no evaluation from the relevant parties. This research aims to provide recommendations for UI/UX design on the Siji Sales Force Website based on the results of analysis using the Design Thinking method. Design Thinking is an approach or method of problem solving both cognitively, creatively and practically to answer human needs as users. Design recommendations are built in prototype form using the Figma application. The prototype that was built was tested for usability using the System Usability Scale (SUS), obtaining a score of category B or "Good" which indicates that the prototype design meets acceptable requirements or is declared acceptable by interested parties. Based on the test results, the design redesign was acceptable and considered effective, so it is hoped that the design created can become a recommendation for the system development team to improve the Siji Sales Force website.